R&D diversification in MNCs: Between earnings management and shareholders increasing wealth - Dhaoui, Abderrazak (Journal of Business Economics and Management, 2008)
This paper examines the impact of the R&D geographic diversification on the shareholders’ wealth (as measured appreciatively by the firm's market value) and on the earnings management as a mechanism of manager's entrainment. Using a sample of 460 firm‐year observations for multinational firms over the 2002–2006 period, we find that the R&D decentralization may enhance the shareholders’ wealth and increase the managers’ one. The results show that the R&D geographic diversification increases the informational asymmetry and support the emergence of the favourable conditions for the earnings management and the managers’ entrainment. It may increase the managers’ autonomy which likely allows them to manage the result in order to increase their own wealth and destruct the shareholder's one.First published online: 14 Oct 2010